Impact of the COVID-19 pandemic on young people living with HIV in Lesotho: a qualitative study - Michelle E Robinson; Thomas Shepherd; Maema Ramaema; Moraoetsi Rakuoane; Ntoli Moletsane; Rafiloe Mpholo; Graham Leigh (BMJ Publishing Group, 2024)
Introduction There is a growing body of research evidencing the detrimental impact of the COVID-19 pandemic on the mental health and well-being of young people. This impact may be worse in low-resource settings, especially those in sub-Saharan Africa, where pandemic impacts may be exacerbated by poverty, limited healthcare access and other health epidemics including HIV. We explored the COVID-19 pandemic impacts on young people living with HIV in Lesotho to understand the experiences of HIV management, well-being, financial stability and education status.Methods Thirty-one semistructured, face-to-face interviews were conducted with young people aged 15-19 years of age living with HIV from eight districts across Lesotho. Interviews were conducted in Sesotho, audio-recorded, later transcribed and translated to English prior to analysis. Analysis consisted of a thematic analysis using principles of constant comparison to explore key and emerging themes.Results Analysis revealed five major themes: 'financial instability and food insecurity', 'challenges to health and well-being', 'changing relationship dynamics', 'loss of educational opportunities' and 'understanding the threat of COVID-19'.Conclusions While participants discussed being able to access antiretroviral therapy, this study highlights the significant impact of the COVID-19 pandemic and associated lockdown measures on the mental health and well-being, financial stability and educational development of young people living with HIV in Lesotho.